Biological Control of Rice Sheath Blight Disease (Rhizoctonia solani) Using Bio-pesticides and Bio-control Agents (Bangladesh Rice Journal, 2021)
A series of experiments were conducted in Plant Pathology Laboratory at Bangladesh Rice Research Institute (BRRI), Gazipur to know the efficacy of four bio-pesticides Recharge, Microtech1, Agroplus and Chitin and two bio-control agents (Trichoderma harzianum and Bacillus subtilis) on the major rice disease sheath blight (ShB) caused by Rhizoctonia solani in in-vitro and field condition. One fungicide Nativo (Tebuconazole 50% + Trifloxystrobin 25%) and one disease control (without any treatments) were also included as treatment for comparison. Radial mycelia growth of R. solani was mostly inhibited by a Bangladesh Trichoderma harzianum (BT1), Recharge and chemical fungicide Nativo 75 G at 48 hours of dual contact of R. solani and tested bio-pesticides or bio-control agents in in-vitro. The other bio-pesticides along with B. subtilis didn’t show any inhibition effect on the mycelia growth of R. solani which was similar to control (only water) treatment. Fungal inhibition 87.5% and 86.3% of Rhizoctonia solani was obtained by Recharge and Trichoderma harzianum (BT1), respectively which was nearly similar to the chemical treatment Nativo (96.3%) in in-vitro dual culture method compared to control treatment. In net house condition, 74% sheath blight disease was inhibited by soil application of Recharge (0.3 g/m2 with 50 ml water) for two times at the time of transplanting and 30 days after transplanting (DAT), whereas similar soil application of B. subtilis (OD600=0.3) was not found effective to control the ShB disease (< 30% disease reduction). The highest ShB disease was reduced by the chemical control Nativo 75 G (94.2%) followed by BT1 (89%), bio-pesticide Recharge (70.8%), Microtech1 (37.4%) and Chitin (61.3%) compared with the disease control when the tested materials were sprayed for two times (3 days before and 4 days after inoculation).Bangladesh Rice J. 24 (1): 47-58, 2020